Exploring the collective process of classroom dialogue using sequential pattern mining technique - Song, Yu; Cheng, Bo; Zhu, Jia; Hu, Xiaoyong (International journal of educational research, 2022)
•Classroom dialogue is widely used for teaching, and relates closely to teaching productiveness.•Demonstrate sequential patterns of classroom dialogue.•Dialogic sequences for mathematics, science and literacy lessons shared commonalities abeit maintained characteristics.•Dialogue concerning prior knowledge and analysis were essential intermediary point of long sequences.•Increase teachers’ management skills for a constructive and productive dialogue. Classroom dialogue is a widely used method for teaching and teacher's skills in managing dialogue matters closely to the productiveness of lessons. This study explores the sequential patterns of classroom dialogue and reveals how contributions are built collectively. There were commonalities in the dialogic sequences of the three subjects although they maintained their own characteristics. Talk concerning previously learnt knowledge and analysis tended to be initiations or follow-ups of other kinds of dialogue in the three subjects. Prominent long sequences in science lessons revealed high levels of cognition, which tended to start from elaboration, then triggered comparison and a summary of content, and finally gave rise to discussion about how to apply knowledge to solve novel problems.